Physical Activity Participation of Disabled Children: A Systematic Review of Conceptual and Methodological Approaches in Health Research - Ross, Samantha Mae; Bogart, Kathleen R.; Logan, Samuel W.; Case, Layne; Fine, Jeremiah; Thompson, Hanna (Frontiers in Public Health, 2016)
Physical activity participation is widely recognized as a critical component of health and development for children with and without disabilities. Emergent literature reflects a paradigm shift in the conceptualization of childhood physical activity as a multi-dimensional construct, encompassing aspects of physical performance and self-perceived engagement. However, ambiguity remains around how participation as a health construct is integrated into physical activity research. The primary objective of the present mini-review is to critically examine current conceptual and methodological approaches to examining physical activity participation among children with disabilities. We conducted a systematic review of contemporary literature (published between 2000 and 2016). 17 articles met inclusion criteria and their research approach was classified into guiding framework, definition of the key construct, and measurement used. The primary guiding framework was the International Classification of Functioning, Disability and Health. An explicit definition of physical activity participation was absent from all studies. Eight studies (47%) operationalized physical activity and participation as independent constructs. Measurements included traditional performance-based aspects of physical activity (frequency, duration, intensity), and alternative participation measures (subjective perception of involvement, inclusion or enjoyment). 64% of included articles were published in the past two years (2014-2016) indicating a rising interest in the topic of physical activity participation. Drawing from the broader discussion of participation in the literature we offer a working definition of physical activity participation as it pertains to active, health-associated behaviors. Further description of alternative approaches to framing and measuring physical activity participation are offered to support effective assessment of health status among disabled children.